Understanding language and cognition through bilingualism in honor of Ellen Bialystok - Luk, Gigi; Anderson, John A.E; Grundy, John G. (John Benjamins Publishing Company, 2023)
"Bilingualism is a ubiquitous global phenomenon. Beyond being a language experience, bilingualism also entails a social experience, and it interacts with development and learning, with cognitive and neural consequences across the lifespan. The authors of this volume are world renowned experts across several subdisciplines including linguistics, developmental psychology, and cognitive neuroscience. They bring to light bilingualism's cognitive, developmental, and neural consequences in children, young adults, and older adults. This book honors Ellen Bialystok, and highlights her profound impact on the field of bilingualism research as a lifelong experience. The chapters are organized into four sections: The first section explores the complexity of the bilingual experience beyond the common characterization of "speaking multiple languages." The next section showcases Ellen Bialystok's earlier impact on psychology and education; here the contributors answer the question "how does being bilingual shape children's development?" The third section explores cognitive and neuroscientific theories describing how language experience modulates cognition, behavior, and brain structures and functions. The final section shifts the focus to the impact of bilingualism on healthy and abnormal aging and asks whether being bilingual can stave off the effects of dementia by conferring a "cognitive reserve.""--
Keywords: Neurowissenschaften; Zweisprachigkeit; Kognitive Linguistik; Psycholinguistik; Bilingualism / Psychological aspects; Psycholinguistics; Cognition; Festschriften; Aufsatzsammlung